2017
DOI: 10.1242/jeb.146951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photophase illuminance on locomotor activity, urine production and urinary 6-sulfatoxymelatonin in nocturnal and diurnal South African rodents

Abstract: Effects of photophase illuminance (1, 10, 100 and 330 lx of white incandescent lighting) on daily rhythms of locomotor activity, urine production and 6-sulfatoxymelatonin (6-SMT; 10 versus 330 lx) were studied in nocturnal Namaqua rock mice (Micaelamys namaquensis) and diurnal four-striped field mice (Rhabdomys pumilio). Micaelamys namaquensis was consistently nocturnal (∼90-94% nocturnal activity), whereas considerable individual variation marked activity profiles in R. pumilio, but with activity mostly prono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…We first set out to determine the impact of increasing daytime light intensity on circadian rhythms in behavior (general locomotor activity and voluntary wheel-running activity) and physiology (Tb) under stable entrainment to a 12:12 LD cycle. As a previous study in this species failed to identify a pronounced impact on rhythmicity across a range of lower illuminances ( 29 ), here we applied daytime irradiances ( Fig. 1 A ) extending into the lower portion of the natural daylight range (12.77 to 14.80 log melanopsin effective photons/cm 2 /s; or 18 to 1,940 lx Melanopic EDI [equivalent daylight illuminance]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first set out to determine the impact of increasing daytime light intensity on circadian rhythms in behavior (general locomotor activity and voluntary wheel-running activity) and physiology (Tb) under stable entrainment to a 12:12 LD cycle. As a previous study in this species failed to identify a pronounced impact on rhythmicity across a range of lower illuminances ( 29 ), here we applied daytime irradiances ( Fig. 1 A ) extending into the lower portion of the natural daylight range (12.77 to 14.80 log melanopsin effective photons/cm 2 /s; or 18 to 1,940 lx Melanopic EDI [equivalent daylight illuminance]).…”
Section: Resultsmentioning
confidence: 99%
“…A challenge to studying the impact of daytime light exposure in common laboratory models (mice, hamsters, and rats) is that they are nocturnal and employ strategies to avoid light in the day (such as curling up asleep). We therefore used a diurnal rodent, Rhabdomys pumilio (the four-striped mouse) ( 27 29 ) which is active through the day in both the laboratory and wild, ensuring good exposure to modulations in daytime light intensity. We find that increasing irradiance across a range equivalent to that from dim indoor lighting to natural daylight enhances the reproducibility and robustness of behavioral and physiological rhythms at the whole-animal level that persist into subsequent free run in constant darkness.…”
mentioning
confidence: 99%
“…We investigated a diurnal and a nocturnal rodent species, aiming to evaluate the daily rhythms in urine production, urinary 6-sulfatoxymelatonin (6-SMT) and glucocorticoid metabolite (uGCM) concentrations in response to three different photophase wavelengths. In a previous study, we showed that changes in light intensity of the photophase did not affect locomotor activity, urine production or urinary 6-SMT in the same manner in M. namaquensis and R. pumilio (Van der Merwe et al, 2017). These variations could stem from differences in the SCN response to light of different intensities and wavelengths (Bonmati-Carrion et al, 2017;Dkhissi-Benyahya et al, 2000;Oosthuizen et al, 2010), and most likely reflected adaptations to the vastly distinct photo-environments of the temporal niches to which these two species are confined in their natural habitats.…”
Section: Discussionmentioning
confidence: 72%
“…We first set out to determine the impact of increasing daytime light intensity on circadian rhythms in behaviour (general locomotor activity and voluntary wheel running activity) and physiology (body temperature, Tb) under stable entrainment to a 12:12 light:dark (LD) cycle. As a previous study failed to identify a pronounced impact on rhythmicity across a range of lower illuminances (19), here we applied daytime irradiances ( Fig.1A) extending into the lower portion of the daylight range [12.77 to 14.80 log melanopsin effective photons/cm 2 /s; or Melanopic EDI (equivalent daylight illuminance) of 17.92 to 1941.7 lx]. Lighting conditions aimed to reproduce the Rhabdomys experience of natural daylight by approximating the relative activation for melanopsin, rod opsin and cone opsins ( Fig.1A; although note that we were unable to recreate levels of near UV required to adequately stimulate S-cones).…”
Section: Enhancing Daytime Irradiance Increases Reproducibility and Rmentioning
confidence: 66%
“…A challenge to studying the impact of daytime light exposure in common laboratory models (mice and rats) is that they are nocturnal and employ strategies to avoid light in the day (such as curling up asleep). We therefore used a diurnal rodent, Rhabdomys pumilio (the four striped mouse) (17)(18)(19) which is active through the day in both the lab and wild, ensuring good exposure to modulations in daytime light. We find that increasing irradiance across a range equivalent to that from dim indoor lighting to natural daylight enhances the reproducibility and robustness of behavioural and physiological rhythms at the whole animal level.…”
Section: Introductionmentioning
confidence: 99%